Videooculography “HINTS” in Acute Vestibular Syndrome: A Prospective Study - Korda, Athanasia; Wimmer, Wilhelm; Zamaro, Ewa; Wagner, Franca; Sauter, Thomas C.; Caversaccio, Marco D.; Mantokoudis, Georgios (Frontiers in Neurology, 2022)
Objective: A three-step bedside test (‘HINTS’: Head Impulse-Nystagmus-Test of Skew), is a well-established way to differentiate peripheral from central causes in patients with acute vestibular syndrome (AVS). Nowadays, the use of videooculography (VOG) gives the physicians the possibility to quantify all these eye movements. Goal of this study is to compare the accuracy of the VOG “HINTS” (vHINTS) to an expert evaluation. Methods: We performed a prospective study from February 2015 until September 2020 on all patients presenting at the emergency department (ED) with signs of an AVS. All patients underwent clinical HINTS (cHINTS) and vHINTS followed by a delayed MRI, which served as a gold standard for stroke confirmation. Results: We assessed 46 AVS patients, 35 acute unilateral vestibulopathy patients (AUVP) and 11 stroke patients. The overall accuracy of vHINTS to detect a central pathology was 94% with 100% sensitivity and 88.9% specificity. Experts, however, assessed cHINTS with a lower accuracy of 88%, 90.9% sensitivity and 85.7% specificity. The agreement between clinical (cHIT) and video head impulse test (vHIT) was good, whereas for nystagmus direction was fair. Conclusions: vHINTS proved to be very accurate in detecting strokes in AVS patients, with 9 %points better sensitivity than the expert. The evaluation of nystagmus direction was the most difficult part of HINTS.